Development study usage evaluation LKPD based inquiry learning - Rian Vebrianto; Radeswandri Radeswandri; Mery Berlian; M. Alfikri Romadan (Universitas Negeri Yogyakarta, 2023)
Student worksheets (LKPD) are teaching material sheets that contain tasks that are arranged mathematically according to the level of knowledge and age of students in easy-to-understand language, so that they can study independently with a little help and guidance from the teacher. With the many uses of these teaching materials, this study aims to evaluate the use of student worksheets among students as a means of education and promotion. The research method used in this research is development research using the 4D model but only limited to the response test or evaluation of the use of LKPD. The research was conducted by involving 35 students from various study programs. The data collection tool used is an online questionnaire consisting of 5 constructs with 27 questions related to evaluating the use of LKPD. The collected data were then analyzed using SPSS version 23.00 for windows. The results showed that the students' evaluation of the use of LKPD in the five constructs had an average of 3.98 in the good category. Recommendations for further research are that it is necessary to conduct an initial study first to test the effectiveness of using inquiry learning based worksheets.